Hubungan Self Efficacy Terhadap Prokrastinasi Guru Pendidik Di SMP N 1 Kretek - Fahmawanti S; Dwi Rio S S; Leo Trihartantyo (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2020)
This study aims to find out the relationship between self-efficacy and procrastination of teachers in Kretek 1 Junior High School with a sample of 34 teachers consisting of female and male teachers. The data collection of the research sample was carried out by random sampling model where every individual in the population gets the same opportunity to become participants for research subjects. This research using the scale of procrastination (Alpha 0.781) and the scale of self-efficacy (Alpha 0.820). Research data analysis was performed by the product moment with SPSS 19 for windows program. The results showed that the correlation coefficient between the two variables was -0,524 with p = 0.001 (<0.05). The results concluded that there was a significant relationship between self-efficacy and procrastination, therefore the hypothesis in this study was accepted.